Optimalisasi Peran Tenaga Kesehatan Dalam Meningkatkan Patient Center Care Sebagai Upaya Pelayanan Terintegrasi - Wati, Ni Made Nopita; Dewi, Ni Luh Putu Thrisna; A.A Sri Sanjiwani; Ketut Lisnawati; I Nyoman Sudarma (Poltekkes Kemenkes Surakarta, 2024)
Background: Health services provided to patients should be integrated so as to ensure patient safety. The paradigm of health services is currently undergoing a change where it no longer prioritizes one profession as the core of service but instead requires the integration of various professions in providing health services. Patient-centered care (PCC) is a patient-focused service that can be carried out through interprofessional communication. The purpose of this service activity is to increase knowledge and optimize the competence of health workers to increase PCC through the implementation of interprofessional communication. Methods: The dedication method used in this activity is through a webinar using the Zoom meeting application. One of the private hospitals in Bali is a partner in this activity. This service activity consists of three stages: preparation, implementation, and evaluation. Results: The results of the activity show that health workers are able to carry out interprofessional communication and improve PCC as an integrated health service. Conclusion: Health workers are able to carry out interprofessional communication in improving PCC as an integrated health service. The community service process went according to plan and all health workers involved played an active role during the activities. It is hoped that health workers will always be able to apply interprofessional communication to improve PCC.